2018
DOI: 10.1186/s12954-018-0232-z
|View full text |Cite
|
Sign up to set email alerts
|

Toots, tastes and tester shots: user accounts of drug sampling methods for gauging heroin potency

Abstract: BackgroundInternationally, overdose is the primary cause of death among people injecting drugs. However, since 2001, heroin-related overdose deaths in the United States (US) have risen sixfold, paralleled by a rise in the death rate attributed to synthetic opioids, particularly the fentanyls. This paper considers the adaptations some US heroin injectors are making to protect themselves from these risks.MethodsBetween 2015 and 2016, a team of ethnographers collected data through semi-structured interviews and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 61 publications
(38 reference statements)
2
50
0
Order By: Relevance
“…Our study also revealed how similar protective and risk mitigation strategies are being taken up to reduce overdose risk, including a variety of behavioral interventions and accessing trusted drug supplies. These findings are consistent with other research that demonstrates how people who use drugs have a high degree of awareness and knowledge about overdose risk, as well as strategies to mitigate this risk [36,37].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study also revealed how similar protective and risk mitigation strategies are being taken up to reduce overdose risk, including a variety of behavioral interventions and accessing trusted drug supplies. These findings are consistent with other research that demonstrates how people who use drugs have a high degree of awareness and knowledge about overdose risk, as well as strategies to mitigate this risk [36,37].…”
Section: Discussionsupporting
confidence: 91%
“…Among people who use drugs more broadly, however, a growing body of literature has described the evolving harm reduction strategies used to mitigate overdose risk in the context of a highly contaminated drug supply. These strategies have included a breadth of behavioral changes, including not using substances alone (i.e., so that peers can assist in the event of an overdose), using one substance at a time, testing the potency of a substance by first using only a small amount, and using fentanyl test strips and other drug-checking technologies 1 to screen for fentanyl contamination in illicit drug compounds [34][35][36][37]. Recent studies have also demonstrated the important role that trustworthy sources of substances play.…”
Section: Introductionmentioning
confidence: 99%
“…Non-medical use of drugs is an epidemic in many parts of the worl d [1][2][3][4]. They are taken into the human body in a wide variety of ways, including smoking, snorting or sniffing powder or solution (intranasal use), inhalation of the heated vapors ("chasing"), orally, and as anal suppositories ("plugging") or injected [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Of these, 10.6 million (range 8.3 million to 14.7 million) were people who inject drugs (PWID) [3]. While all methods of using drugs can be linked with social and health harms, injecting-whether intravenous, subcutaneous, or intramuscular, is the method of administration carrying the highest risk for multiple types of infections, overdoses, and their complications [5,[8][9][10][11]. Injecting drugs also carries high risk of human Immunodeficiency virus (HIV) and viral hepatitis transmission if sterile injecting equipment is not easily accessible and injecting equipment is shared among users.…”
Section: Introductionmentioning
confidence: 99%
“…While different methods of using drugs are associated with social and health harms, injecting -whether intravenous, subcutaneous, or intramuscular, carries the highest risk for multiple types of infections, overdoses, and their complications [37,38]. Injecting drugs also carries signi cantly higher risk of HIV and viral hepatitis transmission especially among users who don't have easy access to sterile injecting equipment and among those who share injecting equipment.…”
Section: Discussionmentioning
confidence: 99%